The League of Nations mandate system – success or failure? - Bar, Agata (Видавництво НДУ ім. Миколи Гоголя, 2019)
The main topic of this article is to analysis the League of Nations mandate system mainly focusing on „B” mandates and an attempt to answer the question whether such system was a success or failure of organization. What is more, research on the topic of mandates will try to show whether today’s unstable situation in Africa resulted, among others, from the activities of the League. The creation of the system in which the states that won the First World War were to progress of poorly developed areas sounds perfect. Undoubtedly, it is creating a better future for indigenous people, however, it is necessary to consider whether the form in which the mandates were able to provide help was appropriate and whether it focused on the development of these areas or even greater use colonizers. For centuries Africa has been used by Europeans as source of natural resources and workforce, the League of Nations plan to improve the transformation of areas colonized in non-sovereign states was a good idea, but you have to remember that the League of Nations survived only to be transformed into United Nations, so it is very short period in relation to the transformation of Africa colonies into independent states.
Keywords: The League of Nations; a mandate system; interwar period; United Nations